Impact of Fear of COVID-19 Pandemic on the Mental Health of Nurses in Pakistan. Issue 5 (4th July 2021) - Khattak, Sajid Rahman; Saeed, Imran; Rehman, Shams Ur; Fayaz, Mohammad
Abstract: The COVID-19 pandemic significantly impacted the mental, emotional and psychological health of Frontline nurses. This study examines the impact of fear of COVID-19 on nurses' turnover intention, secondary trauma, and psychological distress. Additionally, we explore the possible moderating variable, i.e., leadership support that may compensate for the negative impact of fear of COVID-19 on the nurses' turnover intention, secondary trauma, and psychological distress. Initially, 700 nurses were contacted; however, the response of 380 nurses was received. It is found that fear of COVID-19 significantly affects nurses mental health. We concluded that hospital administrations should support, encourage and motivate Frontline nurses to reduce negative emotional and mental health issues.